Human Disseminated Protothecosis: The Skin is the “Window”? - Wang, Xue; Ran, Yuanshuai; Jia, Songgan; Ahmed, Sarah; Long, Xuemei; Jiang, Yinhui; Jiang, Yanping (Frontiers in Immunology, 2022)
Human disseminated protothecosis is a rare infection caused by members of the genus of achlorophyllic algae, always associated with debilitated hosts. Presence of non-budding cells and large, spherical cells (sporangia) with endosporulation (morula) in histology is proof of Prototheca infection. Regrettably, due to the lack of specificity of clinical features and low awareness among clinicians, protothecosis is always underestimated and misdiagnosed. Available data on a species-specific analysis of this infection are limited. In this review, we summarize etiological, epidemiological and clinical aspects of disseminated protothecosis. The potential pathogenicity and clinical differences between P. zopfii and P.wickerhamii were observed. In addition, the skin not only became the main invasion site and involved organ of the pathogen due to its ubiquitous in nature and colonizing the skin. With the increasing numbers of immunocompromised individuals throughout the world, the incidence of disseminated infection caused by Prototheca is bound to increase, and disseminated protothecosis that accompanies skin symptom should be caused more concern by clinicians.